The role of consumer satisfaction, involvement, and engagement on consumer loyalty in the telecommunication industry among Nigerian university students - Ayomide Bello, Sharafa; Osman, Syuhaily; Abd. Rahim, Husniyah; Adewale Yusuf, Sodiq (Human Resource Management Academic Research Society, 2023)
Consumer loyalty is a global issue that most companies are trying to solve. The market nowadays offers consumers a wide range of products and brands to choose from. Consumption has reached a point where consumers have too many options. Thus, understanding consumer purchasing patterns requires involvement and engagement. In today's business world, the business firm must preserve, sustain, and nurture its customer base to enjoy a competitive advantage in the marketplace. This study examines Nigerian telecom customers' satisfaction, involvement, engagement, and loyalty, using 386 students from two universities in Lagos state, which comprise both males and females’ students of the institutions. The hypotheses were tested using Pearson correlation at .001 significance level. The result shows that consumer satisfaction, involvement and engagement help a business concentrate on a particular type of relationship that builds a powerful consumer company connection. From the perspective of the industry, the research has shown that consumer satisfaction, involvement and engagement are one of the key strategies of attaining lasting consumer connection and loyalty. Hence, it was concluded that one of the conditions of true customer loyalty is total satisfaction that is consistent across different angles of industries. As an implication, operators need to promote consumer involvement and be committed to providing reliable services to subscribers, as satisfaction is not only the primary predictor of consumer loyalty.